Modelling the genetic aetiology of complex disease: human-mouse conservation of noncoding features and disease-associated loci - Powell, G; Long, H; Zolkiewski, L; Dumbell, R; Mallon, A-M; Lindgren, CM; Simon, MM (Royal Society, 2022)
Understanding the genetic aetiology of loci associated with a disease is crucial for developing preventative measures and effective treatments. Mouse models are used extensively to understand human pathobiology and mechanistic functions of disease-associated loci. However, the utility of mouse models is limited in part by evolutionary divergence in transcription regulation for pathways of interest. Here, we summarize the alignment of genomic (exonic and multi-cell regulatory) annotations alongside Mendelian and complex disease-associated variant sites between humans and mice. Our results highlight the importance of understanding evolutionary divergence in transcription regulation when interpreting functional studies using mice as models for human disease variants.